The incidence of medium vessel occlusions: a population-based study - Liu, Michael; Nasr, Deena; Brinjikji, Waleed (Frontiers in Neurology, 2023)
The incidence of medium vessel occlusion (MeVO) is not well known. The objective of our study is to perform a population-based assessment to estimate the incidence of MeVOs.Consecutive patients from Olmsted County, Minnesota who presented for acute ischemic stroke seen at Mayo Clinic Hospital from 1/1/2018-12/31/2020 who were found to have a MeVO were included in this study. MeVO was defined as occlusion at or beyond the level of the middle cerebral artery M2 segment, anterior cerebral artery A2 segment, posterior cerebral artery P1 segment, and cerebellar arteries. Census data for Olmsted County was obtained from the United States Census Bureau from the year 2020.1718 patients were screened for the study, 77 patients fulfilled inclusion criteria to be included in the study. Presenting NIHSS was 9 (± 7). The population of Olmsted County was estimated to be 162,847. The incidence rate for MeVO was 16 cases (95% CI 12-19) per 100,000 people per year. Based on estimates of the US population in 2020 of 331,449,281 people, we estimate there are 52,236 (95% CI 40,635-64,002) new cases of MeVOs per year.As the only stroke center in Olmsted County, we have been able to estimate the incidence of ischemic stroke due to MeVO. While the incidence of MeVOs is less than both large and small vessel occlusions, they still represent a significant proportion of strokes with significant morbidity and mortality that would benefit from further studies in both acute intervention and prevention.